The Impact of Customer Reviews, Hotel Location, and Hotel Price Towards Potential Guests’ Intent to Stay at the Ritz- Carlton, Bali - Annarica Tisna; Finny Chianata; Joselyn Chandrigo; Michelle Christy; Valerie (MultiTech Publisher, 2019)
This study examines the influence of customer reviews, hotel location, and hotel price on the intent of potential guests to stay at The Ritz-Carlton, Bali. Through a mixed-methods approach involving surveys, online reviews, and interviews, the research reveals that positive customer reviews significantly contribute to the likelihood of intent to stay, emphasizing the role of online word-of-mouth. Additionally, favorable hotel location emerges as a key driver for guest intent, while the relationship between hotel price and intent proves more complex, indicating a willingness to pay premium prices for positive reviews and desirable locations. These findings provide insights for strategic decision-making in hospitality marketing and management